Centimeter-scale low-damage micromachining on single-crystal 4H–SiC substrates using a femtosecond laser with square-shaped Flat-Top focus spots. Issue 16 (15th August 2021) - Long, Jiangyou; Peng, Qingfa; Chen, Gaopan; Zhang, Yuliang; Xie, Xiaozhu; Pan, Guoshun; Wang, Xiaofeng
Abstract: Femtosecond (fs) lasers have been proved to be reliable tools for high-precision and high-quality micromachining of ceramic materials. Nevertheless, fs laser processing using a single-mode beam with a Gaussian intensity distribution is difficult to obtain large-area flat and uniform processed surfaces. In this study, we utilize a customized diffractive optical element (DOE) to redistribute the laser pulse energy from Gaussian to square-shaped Flat-Top profile to realize centimeter-scale low-damage micromachining on single-crystal 4H–SiC substrates. We systematically investigated the effects of processing parameters on the changes in surface morphology and composition, and an optimal processing strategy was provided. Mechanisms of the formation of surface nanoparticles and the removal of surface micro-burrs were discussed. We also examined the distribution of subsurface defects caused by fs laser processing by removing a thin surface layer with a certain depth through chemical mechanical polishing (CMP). Our results show that laser-induced periodic surface structures (LIPSSs) covered by fine SiO2 nanoparticles form on the fs laser-processed areas. Under optimal parameters, the redeposition of SiO2 nanoparticles can be minimized, and the surface roughness Sa of processed areas reaches 120 ± 8 nm after the removal of a 10 μm thick surface layer. After the laser processing, micro-burrs on original surfaces are effectively removed, and thus the average profile roughness Rz of 2 mm long surface profiles decreases from 920 ± 120 nm to 286 ± 90 nm. No visible micro-pits can be found after removing 1 μm thick surface layer from the laser-processed substrates.